Biotechnology for rural development: Scopes of economic advancement using biotechnology in perspective of rural Bangladesh - Tanzi, Afruza Khatun (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2022.